Simulasi dinamik sistem reaktor eksotermal adiabatik dengan alat penukar panas umpan-keluaran (FEHE) - Tri P. Adhi; Gandi R. Setyadi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2006)
A study of dinamics behavior on adiahatic exothermal reactor with a Feed-Effluent Heat Exchanger (FEHE) is reported in this paper. In practice of a chemical proces industries, configuration of the heat integration of FEHE system are easi to found at process that involving adiabatic exothermal reactor with the demand of feed's heating and of reactor product's cooling. The FEHE system configuration increase the process thermal efficiency throught the use of heat flow on the reactor product to raise the temperature of reactor feed flow. From the steady state economical point of view, this off cource be very interesting to be implemented, althought controlling and operational considerations are need to be taken into account to keep those advantages un-eliminted by operational and controlling matters. The dynamic simulation can give some illustration on how the hehavior of process operation at FEHE system is. Dynamically this system can be examined so that the boundary of operational parameter which could mantain its stability and trigger unstable system can be known and determined. In this study, the simulation of dynamic and steady state condition on system of FEHE-adiabatic exothermal reactor has been performed by assist of process simulator Aspen-Hysys using ammonia synthesis as the model process. The examined un-stable case were the harmonic osilation phenomena on the operational temperature condition. The objective of this study was to obtain a mathematical correlation model that can be applied in predicting when the un-stable phenomena might be happen.Keywords: FEHE System, Oscillation Temperature, Unstabilize Operation AbstrakSebuah kajian mengenai kelakuan dinamik sistem reaktor eksothermal adiabatik dengan alat pertukaran panas umpan-keluaran (Feed-Effluent Heat Exchanger, FEHE) disampaikan pada makalah ini. Dalam praktek industri proses kimia, konfigurasi integrasi pwws sistem FEHE mudah ditemukan pada proses yang melihatkan reaktor eksothermal adiahatik, dengan kehutuhan pemmw.\·anlfiiiJHIII reaktor dan pendinginan produk reakt01 Konfigurasi sistem FEHE memherikan pening/wtan efisiensi thermal proses melalui pemanfctatan a/iran panas produk reaktor untuk menaikkan tempera fur a/iran umpan reakt01 Dari sudut pmzdang ekonomi sistem tunak, lentu saja hal tersehut sangat menarik 1111/uk diimplemen/asilwn, a/am tetapi pertimhangan-pertimhangan operasi dan pengendalian harus diperhatikan agar keuntungan ini tidak lere/iminasi oleh permasalahan-permasalahan pengendalian dan pengoperasian. Simulasi dinamik dapat memherilwn gmnbaran hagaimana kelalwan operasi proses pada sistem FEHE. Secara dinamik, sistem ini dapat diuji sehingga batas-batas parameter operasi vang menjaga kestahilan danmemicu ketidakstahilan dari sis/em dapat diketaluti dan ditentukan. Dalam kajiwz ini simulasi kondisi lunak dan dinamik. sistem reaktor eksothermal adiahatik-FEHE dilakukan dengan hantzwn simulator proses Aspen-Hv.1ys dengan mengamhil sintesi.1· amoniak sehagai model proses. Kasus ketidak-stabilan yang dikaji adalah jetwmena osilasi harmonik kondisi tenzperatur operasi. Tujuan yang hendak dicapai dari kajian ini adalah untuk mendapatkan suatu model korelasi matematik yang dapal digunalwn untuk mcmprediksi kapan saat terjadinyafenomena ketidak-stahilanlersehut.Kata kunci: Ketidak-stabilan Operasi, Osilasi Temperatur, Sistem FEHE